(untitled) (Economics and region, 2025)
The purpose of this research is to examine innovative models of food delivery in the Ukrainian restaurant business market. To achieve this goal, several key tasks have been identified, including an analysis of food delivery models, an exploration of major trends in this segment, and a comparative analysis of the primary market participants. A classification of different food delivery models is proposed. Particular attention is devoted to studying consumer behavior. This approach enables a deeper understanding of the preferences, expectations, and habits of customers utilizing delivery services. Additionally, the study includes the positioning of local and international companies that actively compete and influence the development of the food delivery market. Based on the findings, the research identifies the key challenges facing the food delivery market in Ukraine and outlines prospects for its further development.